THE PRINCIPLE OF CAUTION FOR TEMPORARY OFFICIAL LAND DEED MAKERS (PPATS) IN THE CREATION OF BUYING AND SELLING DEEDS - Rama Dwijaya; Khoidin Khoidin; Moh. Ali (Jurnal Scientia, 2023)
This research with the title Principles of Caution for Officials Making Temporary Land Deeds in Making Sale and Purchase Deeds. PPAT While carrying out legal action, you must always act carefully before making a deed. This research has three problem formulations, namely first, whether the Temporary Land Deed Making Official has complied with the precautionary principle in making the sale and purchase deed, secondly what form of responsibility the Temporary Land Deed Making Official has for deeds that have been canceled by the Court and thirdly what are the future arrangements related to preparation of a sale and purchase deed made by the Temporary Land Deed Official to comply with the precautionary principle. The method used in this research uses normative research methods. The conclusion of this research is that there are still many cases that occur due to the negligence of the Temporary PPAT in issuing authentic deeds. The precautionary principle in Temporary PPAT must be carried out correctly. So that the authentic deed issued by the Temporary PPAT is not invalidated by the Court. Apart from that, the concept of future arrangements should be changed so that the Temporary PPAT can be even better.